THE FROMMELT ATTITUDES TOWARD CARE OF THE DYING CARE FORM B (FATCOD B) INDONESIA VERSION: MEASUREMENT VALIDITY USING FACTOR ANALYSIS IN NURS ING STUDENTS - Muhamad Zulfatul A'la (NurseLine Journal, 2016)
Analysis of nursing students' attitudes towards caring for the dying patient needs to be explored. The Frommelt Attitudes Toward Care of the Dying Care Form B (FATCOD-B) has not previously been adopted and used in the Indonesian language. The aim of this study was to determine the reliability, validity and factor analysis of FATCOD-B Indone sian version (FATCOD-B-I). A descriptive and cross-sectional was used. Reliability test was using Cronbach's alpha coefficient, the validity was using the Pearson correlation and confirmatory factor analysis (CFA). Factor analysis of FATCOD-B-I was in accor